Involvement of Local Wisdom as a Value and an Instrument for Internalization of Public Service Innovation - Savira, Evi Maya; Tasrin, Krismiyati (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2018)
Public service innovations in many ways produce better, cheaper and faster services to the customers. However, the process for good public services need a lot of adjustment such as appropriate supporting technology, competent human resources, strong leadership and contextual business process. Above all is how to internalize the innovation as bureaucratic culture and how this reform spirit embedded to their working habit as public services provider. Indonesia has high diversity in term of culture, tradition, languages, religions, etc. This uniqueness can play as positive aspect and as a challenge as well in term of designing public services innovation. Innovation without considering local values will be a challenge, sometimes it allures destructive actions from the stakeholders who felt uninvolved in the process. Sharing the ownership of the innovation is one of the best ways to involve people as part of the change. Local values can be used as medium to facilitating this change. Realizing the importance of local values as instrument to design public services innovation, Denpasar City emerges as one of the most innovative city in Indonesia in terms of innovation in public services whereby Hindu Balinese culture is integrated within their values for bureaucracy, community, and tourism industry. By using triangulation, this study intends to identify (1) what local values contribute positively to the innovation and their role as instrument to internalize the innovation; (2) what kind of strategy taken by the local government to respond to people needs, to mobilize the resources and to adjust any relevant elements for innovation pro people and stakeholders; (3) how coordination has been made by the local government with other stakeholders involved in innovation. As a result, the output of this study will be a model of sustainable, inclusive and contextual innovation based culture.